The multidimensionality of everyday experiences of internationalisation using collaborative autoethnography (CAE): Narratives of belonging and crossing borders of two female sociologists - Moran, Dr Lisa; Kovacic, Dr Tanja (Sociološki pregled, 2024)
This paper elucidates approaches to collaborative autoethnography (CAE) drawing on two female academics’ experiences, who live in Ireland. As Ellis et al., (2011) state, autoethnography ‘seeks to describe and systematically analyse personal experience to understand cultural experience’. We as two female sociologists, retrospectively and selectively analyse experiences with international academic life; borders, cultural norms, and identity. We refer to belonging to explore academic mobility within the contexts of our lives. We explore relationships between enabling/constraining factors contributing to our engagement with knowledge production and belonging to new academic environments outside our places of origin. Tanja’s account documents her doctoral journey from Slovenia to Ireland, learning the host country’s cultural fabrics to engage with academia, leaving and coming home, which did not mean returning to ‘the known’. Lisa’s narrative displays synergies to Tanja’s illuminating emotions upon entering the UK in 2017, when antiimmigrant sentiment was heightened. However, her experiences of returning during COVID-19 disrupted her imaginaries of coming home.Written in a conversational style, we explore commonalities/differences in experiences of international academic careers. This paper illuminates CAE for opening conceptual avenues into multi-layered dimensions of academics’ experiences, illuminating its significance for international Higher Education policy-making.
Keywords: Collaborative Autoethnography; Internationalisation; Biographies; Borders; Belonging; Policy-making